The Hero's Journey of Arthur Curry Character in Aquaman Movie - Juanda, Ahmad; Surya, Satyawati; Nasrullah, Nasrullah (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This research purposes to find the hero’s struggle and the hero’s journey that appeared in Arthur’s journey. In this research, the researcher analyzed one of the characters from the Aquaman movie. In specific, a character, named Arthur Curry, was analyzed through the hero’s journey theory. The data were analyzed with the hero’s struggle theory by George R. Goethals and Scott T. Allison, as a theory, and hero’s journey theory by Joseph Campbel, as another theory. The data were generated from the actions and dialogues from movie script and Arthur's struggle through his journey to become a hero. In conclusion, the research revealed that Arthur experienced all three struggles that mentioned by Goethals and Allison, those are struggle for something with reason, struggle to fight their weakness, and struggle to face the very evil. It also matched ten stages from seventeen stages of hero’s journey by Joseph Campbell and those are the call to adventure, refusal of the call, supernatural aid, the crossing of the first threshold, the belly of the whale, the road of trials, atonement with the father, apotheosis, the ultimate boon, and the crossing of the return threshold. The conclusion that can be drawn is that although there are several stages that Arthur did not go through, his struggle in the story can be considered as a hero’s journey because he succeeded in achieving his goals.